Intraoperative Eye Care: A DNP Project - Samuel, Savannah (My University, 2022)
Corneal abrasions, while rare, are the most common optic injury that occurs in anesthesia practice, and they account for approximately 2-3% of all anesthesia malpractice suits. Corneal abrasions also cause intense discomfort and stress to the patient, resulting in decreased patient satisfaction and increased hospital costs. With no specific protocol or documentation requirements for preventing corneal abrasions during surgical procedures, it is unclear what preventive efforts and guidance are being utilized by anesthesia providers at the partnering facility. The purpose of this quality improvement project was to assess CRNAs’ knowledge, preferences, and practices regarding eye care and corneal abrasion prevention and whether or not they perceived a corneal abrasion quick reference guide as a useful tool for their practice to prevent and treat perioperative corneal abrasions. This project was a pre and post intervention design using a single PDSA cycle. The intervention, a quick reference guide developed by the team using the most up to date literature on perioperative corneal abrasion prevention, was distributed through emails. Pre and post surveys, developed using Qualtrics survey software, assessed attitudes, knowledge, and practices about perioperative corneal abrasions before and after utilization of the quick reference guide. CRNAs perceived themselves as having greater ability to assess the risk factors, diagnose, and treat corneal abrasions after reviewing the quick reference guide. Future studies involving greater numbers of participants and longer trial periods would provide a better understanding of anesthesia provider perceptions of perioperative corneal abrasions. An EPIC macro is another potential avenue to investigate as an effective corneal abrasion prevention technique.
Keywords: anesthesia, corneal abrasion, surgical patients, anesthesia providers